Learning cultures: some reflections in the context of lifelong learning - Ewa Przybylska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
Cultures of human life worlds, including learning cultures as well, determine the educational activity of social groups and individuals. Some of them favor the development of creativity and animate lifelong learning, whereas others create barriers difficult to break, destroying life and professional chances of young people on the threshold of adulthood. The article takes several threads appearing in the contemporary debate on the cultures of learning. With reference to Jürgen Reichen's concept of literacy, it formulates the question about the limits of pedagogical experiments implemented for the sake of the development of creative personality and creativity of future employees.